A measurement scale for food festival visitor experience. Issue 3 (3rd July 2017) - Ding, Ding; Lee, Hoffer M.
Abstract: The arrival of the experience economy has diversified patterns of consumption, especially in tourism. Tourists travel more to seek the pleasure of new feelings, confirmation of their personality and realization of their self-worth. Food is one of the most basic elements of tourism consumption, and plays a pivotal role in tourism activities. Food festivals have in turn become a popular place for tourists to gather, and an area of growing interest among tourism scholars. Despite the growing body of literature dealing with food festivals however, there is limited information available on the measurement of food festival visitor experience. This paper attempts to fill this gap by developing a multiple-item scale to measure food festival visitor experiences. A questionnaire was designed to survey visitors attending the 14th Macau Food Festival. Following the construction procedure suggested by Robert F. DeVellis, an experiential scale was finalized with 20 embedded items in five dimensions: entertainment, food culture, nostalgia, stress relief and healthy diet education. The scale was tested for its internal consistency and validity. The findings provide tourism practitioners with a better understanding of the experiential features of food festivals, and assist them with more effective market segmentation and experiential product development.